PENYULUHAN DAN PRAKTEK SADARI UNTUK DETEKSI DINI KANKER PAYUDARA PADA REMAJA PUTRI DI PANTI ASUHAN AL-AKBAR PEKANBARU - Elmia Kursani; Raviola Raviola; Yuni Purwanti (COVIT (Community Service of Health), 2022)
Adolescence is a period of transition from childhood to adulthood, where there is dynamic and rapid growth and development in physical, psychological, intellectual, social, sexual behavior associated with the onset of puberty. Problems related to adolescent reproductive health include breast cancer and cervical/cervical cancer. Cancer is one of the biggest causes of death in the world. Based on data from the Global Burden of Cancer (GLOBACAN) released by the World Health Organization (WHO) states that the number of cases and deaths from cancer until 2018 was 18.1 million cases and 9.6 million deaths in 2018. Cancer deaths is estimated to continue to increase to more than 13.1 million in 2030. According to the Ministry of Health (2019), the incidence of breast cancer is 42.1/100,000 population with an average death rate of 17/100,000. Meanwhile, according to the Basic Health Research (Riskesdas) in 2018, the prevalence of cancer in Indonesia reached 1.79/1000. This service aims to determine the description and early detection of breast cancer in adolescents. The method used in the service is to conduct counseling and practice BSE on young women at the Al Akbar Orphanage Pekanbaru. It is hoped that with this BSE counseling and practice, the knowledge level of young women will increase and make them more concerned about their health condition. The results of this service will be published in the community service proceedings.   Keywords: Early detection, breast cancer, young women